Seismicity parameters of Nepal by cumulative slope point change method - Khanal, Ramesh; Shrestha, Radhesh; Chhetri, Pawan; Pradhan, Bharat (Journal of Engineering Issues and Solutions, 2023)
Nepal is one of the most seismically active countries with several seismic sources that are capable of generating moderate to high magnitude earthquakes. In this study, earthquake catalogue was developed by considering six major source zones. The completeness time period was determined by performing sensitivity analysis for various magnitude bin widths and time intervals. The seismicity parameters were computed by the least square method (LSM) and maximum likelihood method (MLM). LSM was based on Gutenberg Richter’s scale relationship, whereas for the maximum likelihood method, it was performed by a new method called cumulative slope point change method (CSPCM). The CSPCM was introduced to account the drawbacks of maximum curvature method (MCM), especially for bulk number of data. Furthermore, paper compares the LSM and the MLM for the calculation of seismicity parameters. The comparison shows that the proposed CSPCM based on MLM is reliable in terms of theoretical and analytical way as compared to LSM and MCM.